CONTROLLING THE ACCURACY OF CUTTING OF WORM WHEELS WITH ASSEMBLED WORM MILLS WITH TWO PARTS OF THE TOOL RAIL PROFILE - SHCHERBYNA, KYRYL; ZAIKA, ANDRII; ZAIKA, SERHII; MAZHARA, VITALII; SKIBINSKYI, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Solving the scientific problem of controlling the accuracy of cutting worm wheels with prefab worm cutters with a tool rail profile divided into two parts will contribute to the expansion of the use of such a metal cutting tool in the conditions of modern machine tool construction.. The practical use of developed worm cutters with a divided profile of the tool rail into two parts in height for processing worm wheels of machine tool equipment makes it possible to increase both the productivity of mechanical processing and to achieve accuracy sufficient for their use in machine tool construction The article analyzes known ways of controlling the accuracy of cutting worm wheels with worm cutters and methods of cutting them, as well as analyzes known designs of prefabricated worm full-profile cutters and those with a divided tool rail profile. The features of dividing the tool rail profile into two parts in height have been studied. A new scheme for dividing the tool rail profile of prefabricated worm mills has been developed. A new equation for the overlap between the teeth of the first and second passes has been proposed, which takes into account the radius of rounding of the tops of the teeth of worm mills. A new equation for the overlap between the teeth of the first and second passes is proposed, which takes into account the radius of rounding of the tops of the teeth of worm cutters. A new division of the profile of the tool rails of prefabricated worm cutters is developed. The amount of faceting of the teeth of worm wheels, which will be processed by new prefabricated worm cutters, is analytically determined. The minimum number of tool rails for prefabricated worm cutters has been determined, which at the cutting tool design stage makes it possible to control the accuracy of cutting worm wheels with prefabricated worm cutters with a tool rail profile divided into two parts in height. The possibility of controlling the accuracy of cutting worm wheels by prefabricated worm cutters with a tool rail profile divided into two parts in height at the stage of designing the cutting tool has been confirmed.